UPAYA PENINGKATAN HASIL BENIH PADI ORYZA SATIVA. L) PADA BERBAGAI TARAF GENANGAN AIR DAN TAKARAN VERMIKOMPOS DI LAHAN SAWAH IRIGASI ENTISOL - Nugrohotomo, Nugrohotomo; Yudono, Prapto; Syukur, Abdul (Jurnal Ilmu-Ilmu Pertanian, 2009)
The field research that was designed to study the effect of submerged level and vermicompost dosage to the quantity and quality of paddy seeds (Oryza sativa L) yield on irigated Entisol rice field was conducted from February 10"', 2007 to May 28'', 2007 in the Kadirojo farmer's ricefield, Purwomartani village, Kalasan District, Sleman, Yogyakarta. The location of experiment had entisol soil type, the average annual rainfall of 2075 millimeters in Oldeman, C3 climate classification, at an elevation of 110 meters above sea level. The research was carried out using 3 x 3 factorial experiment regulated by three replication of Split Plot Design. The level of submerged rice soil in vegetative phase (A) is main factor consisting of three level treatments, namely A1 = 6 days damp + 3 days submerged condition, A2=12 damp + 3 days submerged condition and A3= completely submerged condition in vegetative phase. The dosage in vermicompost as the sub factors consisted of three. level of treatments (T) that is T1 = 1 ton, T2 = 2 tons, and T3 = 4 tons hectare-1 The result of the experiment showed that among submerged rice soil vegetative phase treatments, A2 treatment provided the highest paddy seeds yield (6,97 tons hectares-1 a=5%) and among the dosage of vermicompost treatment T2 = 2 tons and T3 = 4 ton tons hectares-1 had significant influence to obtain the highest paddy seeds yield (6,75 and 7,12 tons hectares-t a=5%). Submerged level treatment and vermicompost dosage had no effect on the quality of paddy seed. There wes no interaction treatment between submerged level rice soil vegetative phase and the dosage of vermicompost.